UV SPECTROPHOTOMETRIC QUANTITATIVE ANALYSIS OF FLAVONOID CONTENT IN LAVENDER (LAVANDULA SPP.) GROWN IN UZBEKISTAN - Zokirjonov A; Jalilov F; To’ychiyev G (Scholar Express Journals, 2024)
Flavonoids are important secondary metabolites found in plants, known for their diverse biological activities and potential health benefits. Lavender (Lavandula spp.) is a widely cultivated aromatic herb in Uzbekistan, valued for its essential oils and medicinal properties. This study aimed to quantitatively analyze the flavonoid content in lavender samples from various regions of Uzbekistan using UV spectrophotometry. The results revealed significant variations in flavonoid content among the samples, suggesting the influence of environmental factors on phytochemical composition
Keywords: variations; suggesting; metabolites; UV